Notes and comment : UiTM Law Faculty "blooms" into the new millenium : examining with purpose / Mohd Darbi Hashim - Hashim, Mohd Darbi (Faculty of Administratron and Law, 2001)
Ahmad is a first year student reading for a Bachelor of Laws (LL.B) degree. Right now he is in the midst of sitting for the final examination. And before him is the examination paper on the Law of Contract over which he nervously awaits the instruction from the chief invigilator to begin writing the answers. Then it comes. "You may start writing now! The time on the wall clock is now nine o'clock and you shall stop writing at twelve sharp!" Ahmad begins reading the instructions on the front cover of the paper. "This paper contains SEVEN questions," reads the first instruction. "Candidates are required to answer any FOUR of the questions," reads the next. The rest of the instructions prescribe the "dos" and the "don'ts" of the examination room.